2011
DOI: 10.1186/1477-7827-9-16
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HSP90 autoantibodies in sera of infertile women identify a dominant, conserved epitope EP6 (380-389) of HSP90 beta protein

Abstract: BackgroundWe earlier reported a simple specific test for detection of anti-ovarian antibodies in infertile women and identified number of specific molecular and cellular targets of which human heat shock protein 90-beta (HSP90 beta) was found to be the most immunodominant. The present study focuses on prediction and validation of the immunodominant epitope/s of this protein using sera from infertile women having anti-HSP90 autoantibodies.MethodsDelineation of the immunodominant epitopes of HSP90 beta was done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…The antibody titers of pre‐ and post‐immune sera ( n = 30) obtained from the control and experimental group of mice were checked by ELISA as previously described …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The antibody titers of pre‐ and post‐immune sera ( n = 30) obtained from the control and experimental group of mice were checked by ELISA as previously described …”
Section: Methodsmentioning
confidence: 99%
“…Forty microgram of total ovarian protein or 250 ng of recombinant human HSP90 protein (Stressgen, Glanford Ave, Canada) was electrophoretically separated and transblotted onto Nitrocellulose membrane. Blots were processed to check the immunoreactivity of pre‐ and post‐immune sera ( n = 3) diluted to 1 in 10, as previously described . Uniform loading was checked by Western Blotting with anti‐GAPDH antibody (Millipore) diluted to 1:3000 in PBS as per the protocol previously described …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the quest to understand the pathology of this disease, our group developed a specific and sensitive test (Pires et al, ) that helped establish that autoantibodies to heat‐shock protein 90 (HSP90) are observed in 47% cases of AI‐POI and repeated IVF‐ET failures (Pires and Khole, ). Using the sera from these groups of patients, we demonstrated that the EP6 decapeptide was the most antigenic region of HSP90 (Pires et al, ). Immunizing C57BL/6 female mice with the EP6 peptide revealed that autoantibodies interfere with the process of normal ovarian folliculogenesis and affect oocyte and embryo development (Choudhury and Khole, ).…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian insufficiency is associated with ovarian autoantibodies (Luborsky 2002, Forges et al 2006, Sundblad et al 2006, Nelson 2009, Pires & Khole 2009). Specific autoantigens such as HSP90 (Pires & Khole 2009, Pires et al 2011, Choudhury & Khole 2015) and enolase (Sundblad et al 2006) were reported in POF and infertility, although autoantibodies to these antigens also occur as part of the background antibody repertoire in healthy individuals (Pashov et al 2002). Using immune-proteomics, we found several unique autoantigens including Selenium Binding Protein 1 (SBP1) associated with infertility and POF (Edassery et al 2010).…”
Section: Introductionmentioning
confidence: 99%